Arte, grafite e o espaço urbano (Palíndromo, 2013)
This article approaches artistical interventions on urban spaces, which broke with art conventional spaces, producing change regarding conceptions of site, place and space. Discusses Graffiti art work, whose images and grafisms change the scenary of the big cities, and its inserted in cultural institutions spaces.
Keywords: contemporay art; graffiti; space; site